ESTUDO DE ÉXCITONS ESCUROS EM NANOTUBOS DE CARBONO USANDO DOPAGEM: uma abordagem via fotoluminescência - Rodrigues, Célio Diniz (2011)
The low quantum efficiency of photoluminescence observed in semiconducting carbon nanotube has been attributed to the existence of dark excitons. In this work, we performed photoluminescence spectroscopy studies on samples containing practically one type of nanotubes encapsulated by DNA molecules. It was observed the existence of emission peaks (sidebands) at about 137 meV below the E11 excitonic transition (exciton bright). In addition, we observed an excitonic peak at 264 meV, about twice the energy of the first dark exciton. It was observed that the addition of both positive and negative charges causes the quenching of luminescence. Measurements in samples containing various types of SWCNTs encapsulated by SDS were done. A striking feature was the quenching of luminescence with addition of positive charges at a rate of −9.7 Å/nL, while the addition of negative charges promoted the recovery of the luminescence at a much faster rate of +25.6 Å/nL. Besides the direct observation of dark excitons, we found that through selective doping it was possible to identify a large enhancement of the dark excitonic emission compared to the bright one. Our goal was to study the influence of the environmental on the photoluminescence of SWCNTs and thus find a way to highlight the dark exciton emission from the bright exciton basement signal.